Strategy for Improving The Quality of Public Services in The Tompaso District Office - Paendong, Jendry Jurico; Wawointana, Thelma; Mamonto, Fitri (Technium Social Sciences Journal, 2024)
This research aims to find out, analyze, and describe the Strategy for Improving the Quality of Public Services at the Tompaso District Office. The research method used is qualitative descriptive. The number of informants in this study was 4 people. Data collection uses observation, interview, and documentation techniques. Data analysis through data reduction, data presentation, and drawing conclusions. The results of the research show that the performance of the case study public services at the East Tompaso sub-district office is running well. This is supported by the information data that the researchers obtained that: 1) Service Mechanism In providing services to the community it can be said that it has not been optimal. This is reinforced by the information provided by the sub-district head that the service mechanism has been structured and is always implemented by every community, however, the reality is not yet based on the applicable SOP; 2) Facilities and Infrastructure, the facilities used in providing services and producing documents required by the community are inadequate in terms of capacity; 3) Competence of service providers. If the performance of public services is reviewed after the completion time, there is a guaranteed completion time, it is not yet effective and is not based on standards, for several fields in the East Tompaso sub-district there are still some employees who only master their field, not including other fields. Some employees are placed in their fields because there are limited employees who have expertise in their fields.